Horizontal Inequity in the Utilization of Maternal and Reproductive Health Services: Evidence From the 2018 Nigeria Demographic and Health Survey - Aregbeshola, Bolaji Samson; Olaniyan, Olanrewaju (Frontiers in Health Services, 2022)
Background: Maternal mortality and poor reproductive health outcomes remains major public health challenges in low resource countries. The Sustainable Development Goals have proposed new targets to reduce global maternal mortality ratio to 70 per 100,000 live births and ensure universal access to sexual and reproductive health-care servicesby 2030. Inequity in the utilization of maternal and reproductive health services leads to poor reproductive health outcomes and maternal mortality. Despite reduction in global maternal mortality over the decades, the level of maternal mortality remains unacceptably high in Nigeria with limited attention given by governments to addressing health inequities. This study aimed to examine horizontal inequity in the utilization of maternal and reproductive health services in Nigeria. Methods: Secondary data from the 2018 Nigeria Demographic and Health Survey were utilized to examine horizontal inequity in the utilization of maternal and reproductive health services such as postnatal care, delivery by caesarean section, modern contraceptive use and met need for family planning. Equity was measured using equity gaps, equity ratios, concentration curves and concentration indices. All analyses were performed using ADePT 6.0 and STATA version 14.2 software. Results: The overall coverage level of postnatal care, delivery by caesarean section, modern contraceptive use and met need for family planning was 20.81%, 2.97%, 10.23% and 84.22% respectively. There is inequity in the utilization of postnatal care, delivery by cesarean section and modern contraceptive favoring the rich, educated and urban populations. Met need for family planning was found to be almost perfectly equitable. Conclusion: There is inequity in the utilization of maternal and reproductive health services in Nigeria. Inequity in the utilization of maternal and reproductive health services is driven by socio-economic status, education and location. Therefore, governments and policy makers should give due attention to addressing inequities in the utilization of maternal and reproductive health services by economically empowering women, improving their level of education and designing rural health interventions. Addressing inequities in the utilization of maternal and reproductive health services would also be important towards achieving the Sustainable Development Goal targets 3.1 and 3.7.